Dynamics of Urine Electrolytes in Term Neonates during the 1st Week of Life - Sheng-Yuan Ho; Kai-Li Wang; Hueng-Chuen Fan; Jhao-Jhuang Ding (Journal of Medical Sciences)
Background Urine electrolyte assessment is vital for diagnosing and managing neonatal conditions. However, the challenge of urine collection in neonates has resulted in a lack of standardized urine electrolyte reference values. Aim This study seeks to explore the reference levels and potential trends in serum and urine electrolytes to better understand how the kidneys handle these substances. Methods Healthy neonates were prospectively enrolled following normal births. Using biochemical methods, blood and urine samples were collected and analyzed on the 1st and 5th postnatal days. Statistical analysis was performed using descriptive statistics and the Wilcoxon matched-pairs signed-rank test. Results This prospective study enrolled 55 healthy neonates. Significant changes in serum electrolyte concentrations were observed between the 1st and 5th days after birth. Notably, sodium, creatinine, urea nitrogen, and uric acid levels decreased, whereas potassium, calcium, and phosphate levels increased. Urine analysis revealed significant increases in the tubular maximum phosphate reabsorption per glomerular filtration rate and decreases in the fractional excretion of potassium and uric acid by Day 5. Conclusion This study challenges prevailing assumptions about the stability of neonatal urine electrolytes and highlights dynamic changes in the first postnatal week. These insights lay the groundwork for further research into electrolyte disorders in newborns and have potential implications for improving neonatal care practices.